Angiopoietin-1 is essential in mouse vasculature during development and in response to injury - Jeansson, Marie; Gawlik, Alexander; Anderson, Gregory; Li, Chengjin; Kerjaschki, Dontscho; Henkelman, Mark; Quaggin, Susan E. (The Journal of Clinical Investigation, 2011)
Angiopoietin-1/Tek signaling is a critical regulator of blood vessel development, with conventional knockout of angiopoietin-1 or Tek in mice being embryonically lethal due to vascular defects. In addition, angiopoietin-1 is thought to be required for the stability of mature vessels. Using a Cre-Lox conditional gene targeting approach, we have studied the role of angiopoietin-1 in embryonic and adult vasculature. We report here that angiopoietin-1 is critical for regulating both the number and diameter of developing vessels but is not required for pericyte recruitment. Cardiac-specific knockout of angiopoietin-1 reproduced the phenotype of the conventional knockout, demonstrating that the early vascular abnormalities arise from flow-dependent defects. Strikingly, deletion in the entire embryo after day E13.5 produced no immediate vascular phenotype. However, when combined with injury or microvascular stress, angiopoietin-1 deficiency resulted in profound organ damage, accelerated angiogenesis, and fibrosis. These findings redefine our understanding of the biological roles of angiopoietin-1: it is dispensable in quiescent vessels but has a powerful ability to modulate the vascular response after injury.